St. Martin's Summer - Sabatini, Rafael, 1875-1950 (Salt Lake City, UT : Project Gutenberg, 2001)
"St. Martin's Summer" by Rafael Sabatini is a historical novel likely written in the early 20th century. The book revolves around a rich tapestry of characters in a politically charged setting, including the Seneschal of Dauphiny, Lord de Tressan, and a powerful woman, Madame de Condillac, as they navigate a dangerous plot concerning the young Mademoiselle de La Vauvraye and her marriage prospects. The story unfolds with elements of intrigue, romance, and dramatic confrontations set against a backdrop of the complexities of court life. At the start of the novel, we meet Lord de Tressan, the Seneschal, as he is interrupted from his slumber to receive a visit from Madame de Condillac, who seeks his assistance in a matter concerning her young ward, Mademoiselle de La Vauvraye. Their conversation reveals a clash of wills; Madame de Condillac is adamant about keeping control over Mademoiselle de La Vauvraye, while Tressan is caught between his duties as a loyal servant to the Queen and the challenges presented by the Dowager's ambitions. The opening portion sets the stage for the ensuing conflict and the arrival of Monsieur de Garnache, who is tasked with rescuing Mademoiselle de La Vauvraye, further heightening the tension as loyalties are tested and schemes unfold. (This is an automatically generated summary.)
Release date is 2001-05-01
Produced by An Anonymous Project Gutenberg Volunteer, and David Widger
Keywords: Inheritance and succession -- Fiction; France -- Social life and customs -- Fiction; Nobility -- France -- Fiction